Emerging Non-Invasive Therapies and Their Effectiveness in the Comprehensive Management of Prostate Cancer: a Systematic Review of Current Trends and Future Directions - Aditya, Tengku Rizky; Ismy, Jufriady (Newinera Publisher, 2025)
Prostate cancer remains one of the most prevalent cancers globally, with traditional treatments like surgery, chemotherapy, and radiation often causing significant side effects and lengthy recovery. This study explores emerging non-invasive therapies—such as androgen-receptor pathway inhibitors (ARPI), radioligand therapy with lutetium, immunotherapy, high-intensity focused ultrasound (HIFU), and cryoablation—evaluating their efficacy, side effects, progression-free survival (PFS), overall survival (OS), and tumor reduction. A systematic review of recent studies revealed that ARPIs and lutetium-based radioligand therapy significantly improve PFS and OS in metastatic cases. Meanwhile, HIFU and cryoablation show promise in localized prostate cancer, offering effective tumor control with shorter recovery and fewer long-term complications than surgery. Immunotherapy, notably immune checkpoint inhibitors, demonstrated efficacy in select patient groups but posed risks of immune-related adverse events. While these therapies highlight a shift toward personalized treatment—leveraging genomic and clinical markers to optimize patient care—long-term data on their outcomes and side effects remain limited. This review underscores the potential of non-invasive therapies to transform prostate cancer management by enhancing quality of life and reducing treatment burdens. However, extensive research and clinical trials are essential to validate these approaches as standard care.